HCV-induced autophagy and innate immunity - Lee, Jiyoung; Ou, J.-H. James (Frontiers in Immunology, 2024)
The interplay between autophagy and host innate immunity has been of great interest. Hepatitis C virus (HCV) impedes signaling pathways initiated by pattern-recognition receptors (PRRs) that recognize pathogens-associated molecular patterns (PAMPs). Autophagy, a cellular catabolic process, delivers damaged organelles and protein aggregates to lysosomes for degradation and recycling. Autophagy is also an innate immune response of cells to trap pathogens in membrane vesicles for removal. However, HCV controls the autophagic pathway and uses autophagic membranes to enhance its replication. Mitophagy, a selective autophagy targeting mitochondria, alters the dynamics and metabolism of mitochondria, which play important roles in host antiviral responses. HCV also alters mitochondrial dynamics and promotes mitophagy to prevent premature cell death and attenuate the interferon (IFN) response. In addition, the dysregulation of the inflammasomal response by HCV leads to IFN resistance and immune tolerance. These immune evasion properties of HCV allow HCV to successfully replicate and persist in its host cells. In this article, we discuss HCV-induced autophagy/mitophagy and its associated immunological responses and provide a review of our current understanding of how these processes are regulated in HCV-infected cells.